The transformative value chain: rethinking food system interventions - Mechri, Aicha; Hanisch, Markus; Hänke, Hendrik (Frontiers in Sustainable Food Systems, 2023)
Food value chains (VC) are an integral part of food systems, and VC ) programs remain central in the work of development agencies. Despite their popularity among donors and their attempts to tackle food and nutrition security, poverty alleviation and environmental sustainability, food value chain interventions are at crossroads. The ongoing food system crisis has ultimately put a square emphasis on food as a nexus issue. The objective of this paper is to review the history and conceptual basics behind food VC development and to suggest changes in the way interventions are designed and implemented in order to face the current critical juncture of food systems. The paper reviews theoretical as well as empirical underpinnings of contemporary food value chain interventions. Three transformative concepts, i.e., system thinking, transformative capacity and strong sustainability, embedded within agroecological principals, are suggested to replace the traditional paradigm of the sustainable food VC development. A new, principle-based perspective on food value chain development, “the transformative value chain perspective”, is proposed to ensure that future VC promotion contribute to the necessary sustainability transformation of our food systems.